2009
DOI: 10.1590/s0102-311x2009000500023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sexual behavior following a sex education program in Brazilian public schools

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
(19 reference statements)
2
13
0
5
Order By: Relevance
“…Teachers trained to counsel adolescents and their parents about sexual reproductive health issues. 20 These findings are consistent with the findings of other school-based studies among junior high school students in Malaysia, that was effective in enhancing sexual health knowledge, creating a positive attitude toward sexuality, and fostering among students in intervention group the intention to refuse to take sexual risks. 21 Also, a study by Bleakley confirmed that adolescents obtained sexual information from friends, teachers, parents, and media.…”
supporting
confidence: 90%
“…Teachers trained to counsel adolescents and their parents about sexual reproductive health issues. 20 These findings are consistent with the findings of other school-based studies among junior high school students in Malaysia, that was effective in enhancing sexual health knowledge, creating a positive attitude toward sexuality, and fostering among students in intervention group the intention to refuse to take sexual risks. 21 Also, a study by Bleakley confirmed that adolescents obtained sexual information from friends, teachers, parents, and media.…”
supporting
confidence: 90%
“…The critical and symptomatic situation of adolescents' earlier sexual life associated with greater contamination of adolescents and young people with AIDS, in the southern region of Brazil, calls for a broad discussion of what is being done and what should have been done about it [7] and that it will be developed in another article. The point is that sex education is always drifting, and it is strongly influenced by changes in government policies and public opinion [8] [9]. Therefore, it is worrisome that twenty years ago, in 1998, the sex education was officially included, in the Brazilian national school curriculum [10] (the so-called National Curriculum Parameters) as a cross-cutting theme that should be linked to the contents of each school subject, in the primary (from the sixth grade) and high schools.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, alguns estudos, como o realizado pelo Centro Brasileiro de Análise e Planejamento (CEBRAP) e o de Andrade et al (2009), evidenciaram que as informações a respeito das DST/AIDS não estimulam práticas sexuais nem abstinência, mas sim o comportamento sexual responsável. Desse modo, não há nenhuma evidência que suporte o pensamento de evitar a discussão sobre DST/AIDS (ROMERO et al, 2007;COELHO et al, 2011).…”
Section: Abordagens Temáticas Dos Artigosunclassified